CULTIVATION TECHNOLOGY AND PRODUCTIVITY OF SWEET SORGUM IN THE CONDITIONS OF SOUTH KAZAKHSTAN - Alpamyssova, G. B.; Mambetov, К. К.; Baibekov, Е.; Shapаlov, S. K.; Nagiyeva, A. G. (ЗКАТУ им. Жангир хана, 2024)
The article presents research data on sweet sorghum with yield indicators, a heat-resistant, drought-resistant crop in the conditions of Southern Kazakhstan. Sorghum has a wide range of uses and is ranked third in the world as a food plant after wheat and rice. Grain is a valuable feed for livestock and a raw material for the feed, starch, syrup and alcohol industries; It is used as a grain crop in the preparation of cereals and bread. External conditions have both direct and indirect effects on economic growth. It is known that the rate of growth and development of plants depends on the intensity of physiological, metabolic and energy processes, air and root nutrition, moisture exchange, and when they change, the influence of external conditions can affect the growth rate. It should be noted that in natural conditions it is quite difficult to establish which of the factors may have an influence, because they are closely interrelated. In the course of research on the crop under study, the influence of factors is observed not only on their growth and development, but also on the formation of the crop and its quality. Sweet sorghum is tolerant of critical drought, has the ability to preserve biomass during prolonged dry weather, and economically consumes soil moisture throughout the growing season during the formation of vegetative and generative organs. Therefore, this crop is an acceptable silage crop in dry conditions, which provides good security for the uninterrupted in-line production of feed with a high content of feed units and digestible protein during the feeding period of animals. An important biological property and advantage of sorghum is continuous sowing without loss of yield, also sowing on slopes, eroded and saline lands.
Сultivation technology and productivity of sweet sorgum in the conditions of south Kazakhstan / G. B. Alpamyssova, К. К. Mambetov, Е. Baibekov, S. K. Shapаlov, A. G. Nagiyeva. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 2-2 (75). Ч. ІІ. - Р. 61-69 (Uralsk).
Keywords: Biotechnology; bioactive compounds; sweet sorghum; productivity; forage crops; научный журнал; зкату